AEROMYCOLOGICAL INDOOR ENVIRONMENTAL STUDY OF K.T.S. GENERAL HOSPITAL GONDIA, (MAHARASHTRA) INDIA - S.G. KUKREJA,; NITIN B. KATRE,; A.J. MUNGOLE, (The Bioscan, 2025)
Fungal spores in indoor air may come from outdoor by ventilation or they may originate within (Kukreja et. al., 2014). When these spores get favorable conditions they proliferate and cause the deterioration. An aeromycological study verifies the presence and quantifies the concentration of fungal propagules in the air. It is very important in the hospital setting because of the increasing numbers of immune suppressed and severely ill patients (Waghare et al., 2016) .The objective of this study was to determine the concentration of fungi in the air of the different sections like Outdoor Patient Department (O.P.D) Operation Theater (O.T.) and General Ward Section, of K.T.S General Hospital Gondia. The total 1349 colonies were trapped from feb.2023 to Jan 2024 by exposure petriplate method. Out of 1349 colonies, total 508 colonies found in O.P.D, 481 colonies found in General ward and 360 colonies found in Operation Theater of hospital. The maximum fungal spores were recorded in O.P.D. section followed by general ward while minimum fungal spores seen in Operation Theater of K.T.S General hospital Gondia. Total 6990 CFUs/m3 are observed by Hi- media air sampler method. There was 2575 CFUs/m3 found in O.P.D. section while 2370 CFUs/m3 in General Ward and 2045 CFUs/m3 O.T.section. Fungi found in indoor environment of hospital are Aspergillus, Cercospora, Mucor, Penicillium, Rhizoctina, Cladosporium, Rhizopus and Alternaria.